Contrast Sensitivity in Early to Intermediate Age-Related Macular Degeneration (AMD). (1st February 2022) - Ridder, William H.; Comer, George; Oquindo, Caren; Yoshinaga, Pat; Engles, Michael; Burke, James
ABSTRACT: Purpose: Previous studies indicated that advanced age-related macular degeneration (AMD) affects contrast sensitivity (CS) in humans. The CS results for early/intermediate AMD patients are contradictory. The purpose of this study was to determine if CS testing discriminates early/intermediate AMD patients with normal acuity from normal patients. Methods: Forty-nine subjects (25 control and 24 early/intermediate AMD patients) were chosen for this project. The age ( p = .16) and acuity ( p = .34) was not significantly different between the groups. The average simplified AREDS AMD grade for the AMD patients was 2.75 ± 1.03. Three CS functions employing a descending method of limits were measured at the fovea (1. stationary stimulus and, 2. 16 Hz counter-phase stimulus under photopic conditions and 3. the stationary stimulus viewed through a 2 log unit neutral density filter (mesopic condition, background luminance of 1 cd/m 2 )) and at 4 deg right or left of the fovea with a horizontally oriented sine wave grating (5 deg diameter) viewed on a VPixx monitor (luminance of 100 cd/m 2 ). Results: The early AMD patients were no different from the control patients for any test condition. The intermediate AMD patients were significantly different from the control patients for the mesopic CS function ( p = .05). Post-hoc 2-sample t-tests for the intermediate AMD patients were significantly different from the control patients under the stationary photopic and mesopic conditions for the 1.5 cycle per degree stimulus. Conclusions: Group differences in CS were only found in intermediate AMD patients. The loss in CS increased for the intermediate AMD patients under low light levels. Thus, CS may not be the optimal test to discriminate early AMD from control patients so other tests measured under dark adapted conditions should be investigated.